Oral health status of children and adolescents with autism spectrum disorder: A systematic review of case-control studies and meta-analysis. (July 2020) - Lam, Phoebe PY; Du, Rennan; Peng, Simin; McGrath, Colman PJ; Yiu, Cynthia KY
Children and adolescents with autism spectrum disorder are thought to be more vulnerable to oral diseases than typically developing individuals due to cariogenic dietary habits, self-injurious behaviors, and increased barriers to dental care services. This review aimed to summarize current evidence comparing the oral health status of people diagnosed with and without autism spectrum disorder. Study selection and screening, data extraction, risk of bias assessment, and quality-of-evidence evaluation was conducted using the Grading of Recommendations Assessment Development and Evaluation approach and performed independently by two reviewers. A total of 16 studies were found eligible for qualitative synthesis and 15 were included in quantitative analysis. When comparing children and adolescents diagnosed with and without autism spectrum disorder, significantly higher prevalence of bruxism was identified. Individuals diagnosed with autism spectrum disorder were also found to have significantly lower salivary pH. However, no statistically significant differences in terms of caries prevalence and severity, oral hygiene and periodontal status, prevalence of malocclusion, dental traumatic injuries, as well as salivary flow rate and buffering capacity were found. The quality of evidence of each outcome was graded as very low mainly due to the overall high risk of bias, considerable heterogeneity, and imprecision. Lay Abstract: Children and adolescents diagnosed with Autism Spectrum Disorder (ASD) are thought to be more vulnerable to oral diseases than typically-developing individuals. This is due to their increased barriers to dental care services, self-harm behaviors and dietary habits that may favor tooth decay. In this review, we summarized the current evidence comparing the oral health status of children and adolescents diagnosed with and without ASD. After a systematic search in the literature, we found that the salivary pH of individuals diagnosed with ASD was significantly lower, but the results were not clinically significant that can increase their risks to tooth decay. We also found weak evidence suggesting a higher percentage of children and adolescents diagnosed with ASD having the habit of tooth grinding compared with their neurotypical counterparts. When comparing salivary flow rate, tooth decay, gum diseases, tooth malalignment and tooth trauma; no significant differences were found between the two groups. The findings did not suggest ASD as a predisposing factor to oral diseases: other factors including sugary diet and inadequate oral hygiene may play a more important role. We also call for further research to establish more concrete association between ASD and oral diseases.